Cinematic Echoes of Covenants Past and Present National Identity in the Historical Films of Steven Spielberg and Andrzej Wajda - Garbowski, Christopher (Interdisciplinary Studies in Performance, 2018)
The author analyzes appropriately selected historical films of Steven Spielberg and Andrzej Wajda with respect to historical memory in relation to film. Cultural and moral foundations of national identity are also taken into account. Spielberg films particularly valuable for this comparative analysis are: «Schindler's List», «Amistad», «Saving Private Ryan» and «Lincoln»; crucial Wajda films include: «Korczak», «Holy Week», «Katyń and Wałęsa». These works are analyzed in relation to the problem of representing the Holocaust, self-scrutiny in historical memory, commemoration of sacrifices for the national community during war, and foundation myths evoked through national heroes. The larger thematic framework for the above concerns is the underlying sense of covenant present within the two national communities that Spielberg and Wajda draw upon, a sense that explores the possibility of moral renewal under contemporary circumstances.